(untitled) (Journal of Politics and International Studies, 2024)
Striking the delicate balance in Pakistan's foreign policy amidst regional complexities, the researcher thoroughly investigated Pakistan's foreign policy towards its neighbouring countries and how it shifts from one nation to another. The researcher shed light on global leaders' challenges and crises regarding geopolitical complexities. Moreover, the role of Pakistan was discussed to bring stability to the region, particularly in the Muslim world, as a significant Muslim state of the Organisation of Islamic States(OIC). The researcher also studied the current research about ideologies of foreign policies and how these policies may help build firm and working international foreign policy, leading to attaining specific goals and objectives. However, it is a sensitive matter, and any negligence will result in severe consequences. The researcher correlates the two major foreign policy approaches, realism and rationality, and their practical implementation of ineffective foreign policy. The research made a correlation between the foreign policy of Pakistan-Iran and Iran-Saudi Arabia foreign policy, as the two states, the Kingdom of Saudi Arabia and Iran, faced tension in their foreign affairs for an extended period, and this tension reflected in the political scenario in the region as a whole as well. However, the researcher emphasises that good working foreign policy between the Kingdom of Saudi Arabia and the Islamic Republic of Iran will bring political stability in this region and positive developments at the end of the Muslim World to make a strong unity bond between the Muslim states. However, it analysed Pakistan’s tentative foreign policy and action plan in this spectrum. The research aims, and objectives are to advise a policy action plan that helps them build a solid, practical, friendly foreign policy with the neighbouring countries with sustainable economic growth and balance the foreign policy to achieve strategic goals in this region.